IMPACT OF LONG DURATION HIGH-INTENSITY PHYSICAL EXERCISE ON SMALL AND LARGE INTESTINAL FUNCTION IN COMPETITIVE ATHLETES – A LITERATURE REVIEW - Michalina Pastuszka,; Kamil Nieroda,; Bartłomiej Andrzej Sałapski,; Aleksandra Małgorzata Obarzanek,; Michał Nowak,; Natalia Julia Szafraniec,; Dominika Brożyna,; Katarzyna Anna Sobczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Long-duration, high-intensity endurance exercise places unique stress on the gastrointestinal tract. In competitive endurance disciplines such as triathlon, repeated exposure to prolonged exertion, heat strain, and dehydration can disturb normal gastrointestinal physiology. A key response to intense exercise is redistribution of blood flow away from the splanchnic circulation toward working muscles and thermoregulatory tissues, which may reduce intestinal perfusion. When this reduction is marked or sustained, it can contribute to mucosal injury, and subsequent restoration of blood flow may further intensify damage through inflammatory and oxidative processes. These mechanisms can weaken epithelial tight junctions, increase intestinal permeability, and promote translocation of luminal microbial products, potentially amplifying systemic inflammatory responses. Clinically, such changes are reflected by the high prevalence of gastrointestinal symptoms during training and competition, which may limit fueling tolerance and impair performance. In rare cases, more severe outcomes such as ischemic colitis or gastrointestinal bleeding may occur.The aim of this narrative review is to summarize current evidence on how long-duration, high-intensity endurance exercise affects small and large intestinal perfusion, epithelial barrier integrity, and gut microbial ecology in competitive athletes, and to discuss the practical significance of these alterations for symptoms, performance, and adverse gastrointestinal events.Results: Prolonged high-intensity endurance exercise markedly reduces splanchnic perfusion, predisposing the intestine to hypoperfusion and ischemia–reperfusion–related oxidative and inflammatory injury. Therefore, epithelial integrity may be compromised through tight junction disruption and enterocyte damage, resulting in increased intestinal permeability (“leaky gut”) and facilitating translocation of luminal bacterial components with subsequent immune activation. In addition, repeated endurance training and sport-specific dietary patterns appear to modulate gut microbiota composition and function, and some exercise-associated microbial shifts may correlate with metabolic adaptation and endurance performance.Materials and methods: reviewing recent literature research up to 15 years ago based PubMED, Google scholar reaserche based on following key words: leaky gut syndrome in athletes, gut microbiota in athletes, ischemic colitis in athletes.